Expert consensus on neurodevelopmental outcomes in pregnancy pharmacovigilance studies - Bromley, R. L.; Bickle Graz, M.; Bluett-Duncan, M.; Chambers, C.; Damkier, P.; Dietrich, K.; Dolk, H.; Grant, K.; Mattson, S.; Meador, K. J.; Nordeng, H.; Oberlander, T. F.; et al. (Frontiers in Pharmacology, 2023)
Background: Exposure in utero to certain medications can disrupt processes of fetal development, including brain development, leading to a continuum of neurodevelopmental difficulties. Recognizing the deficiency of neurodevelopmental investigations within pregnancy pharmacovigilance, an international Neurodevelopmental Expert Working Group was convened to achieve consensus regarding the core neurodevelopmental outcomes, optimization of methodological approaches and barriers to conducting pregnancy pharmacovigilance studies with neurodevelopmental outcomes. Methods: A modified Delphi study was undertaken based on stakeholder and expert input. Stakeholders (patient, pharmaceutical, academic and regulatory) were invited to define topics, pertaining to neurodevelopmental investigations in medication-exposed pregnancies. Experts were identified for their experience regarding neurodevelopmental outcomes following medicinal, substances of misuse or environmental exposures in utero. Two questionnaire rounds and a virtual discussion meeting were used to explore expert opinion on the topics identified by the stakeholders. Results: Twenty-five experts, from 13 countries and professionally diverse backgrounds took part in the development of 11 recommendations. The recommendations focus on the importance of neurodevelopment as a core feature of pregnancy pharmacovigilance, the timing of study initiation and a core set of distinct but interrelated neurodevelopmental skills or diagnoses which require investigation. Studies should start in infancy with an extended period of investigation into adolescence, with more frequent sampling during rapid periods of development. Additionally, recommendations are made regarding optimal approach to neurodevelopmental outcome measurement, comparator groups, exposure factors, a core set of confounding and mediating variables, attrition, reporting of results and the required improvements in funding for potential later emerging effects. Different study designs will be required depending on the specific neurodevelopmental outcome type under investigation and whether the medicine in question is newly approved or already in widespread use. Conclusion: An improved focus on neurodevelopmental outcomes is required within pregnancy pharmacovigilance. These expert recommendations should be met across a complementary set of studies which converge to form a comprehensive set of evidence regarding neurodevelopmental outcomes in pregnancy pharmacovigilance.